Karakteristik Sengketa Pemilukada Di Indonesia Evaluasi 5 Tahun Kewenangan MK Memutus Sengketa Pemilukada - Rudy, Rudy; Purba, Charlyna (Mahkamah Konstitusi Republik Indonesia, 2014)
This study purports to ascertain the characteristic of the local election disputes in Indonesia by way case study through judgment reviews from 2008 to 2013. The research shows that the characteristic of the local election disputes in Indonesia can be classified as structured, systematic, masive, administrative, and substantive. The disputes of local election has been contributed by both the candidates and organizingelectionsof local eletion.